Chapter L'innovation de produit et les dynamiques de l'offre sur les marchés des étoffes de laine dans la France du XVIIIe siècle. Quelques aperçus quantitatifs et qualitatifs - Villain, Julien (Datini Studies in Economic History, 2022)
The consumption of fabrics in 18th-Century Europe experienced a notable expansion - particularly in France, a major hub for the diffusion of clothing fashions across the continent. Driven by manufacturers and merchants, the supply of new product varieties has been highlighted in several French production areas. However, a general assessment of the scale and rates of product innovation in the market for fabrics has never been attempted. By varying the scales of analysis, from the statistics the French monarchy used to assess production in the various production areas to store inventories, we can try to estimate the secular movements of product innovation. Over the course of the 18th century, the market for medium or poor quality cloths appears to have been particularly dynamic: the proportion of new varieties at the end of the century approximated two-thirds of the stock. There was also a tendency to diversify the supply - which ended up making the "world of goods" difficult to read, many product innovations being present on the market only for a while.